Rapid identification of highly potent human anti-GPCR antagonist monoclonal antibodies. Issue 1 (1st January 2020) - Scott, Martin J.; Jowett, Amanda; Orecchia, Martin; Ertl, Peter; Ouro-Gnao, Larissa; Ticehurst, Julia; Gower, David; Yates, John; Poulton, Katie; Harris, Carol; Mullin, Michael J.; Smith, Kathrine J.; et al.
ABSTRACT: Complex cellular targets such as G protein-coupled receptors (GPCRs), ion channels, and other multi-transmembrane proteins represent a significant challenge for therapeutic antibody discovery, primarily because of poor stability of the target protein upon extraction from cell membranes. To assess whether a limited set of membrane-bound antigen formats could be exploited to identify functional antibodies directed against such targets, we selected a GPCR of therapeutic relevance (CCR1) and identified target binders using an in vitro yeast-based antibody discovery platform (Adimab TM ) to expedite hit identification. Initially, we compared two different biotinylated antigen formats overexpressing human CCR1 in a 'scouting' approach using a subset of the antibody library. Binders were isolated using streptavidin-coated beads, expressed as yeast supernatants, and screened using a high-throughput binding assay and flow cytometry on appropriate cell lines. The most suitable antigen was then selected to isolate target binders using the full library diversity. This approach identified a combined total of 183 mAbs with diverse heavy chain sequences. A subset of clones exhibited high potencies in primary cell chemotaxis assays, with IC50 values in the low nM/high pM range. To assess the feasibility of any further affinity enhancement, full-length hCCR1 protein was purified, complementary-determining region diversified libraries were constructed from a high and lower affinity mAb, and improved binders were isolated by fluorescence-activated cell sorting selections. A significant affinity enhancement was observed for the lower affinity parental mAb, but not the high affinity mAb. These data exemplify a methodology to generate potent human mAbs for challenging targets rapidly using whole cells as antigen and define a route to the identification of affinity-matured variants if required.